(untitled) (Fiep Bulletin - online, 2014)
This descriptive research aims to analyze the Pregnancy Sexuality Questionnaire - PSQ elaboration process. It was used of different theoretical referential, being the process of construction carried through in six stages: definition of the subject and theoretician-conceptual basement, where study deepened on the sexuality and its components was become fulfilled, and on the pregnancy, its physiological and psych-emotional alterations, and defined the constructors; formularization of the objectives of the instrument, being the definite objective as evaluation of the sexuality in the pregnancy, considering the pregnant periods pre-pregnancy, the trimesters and post-partum, by means of thematic categories and respective sexual components, resulting in the data-collecting to trace sexual profile of the pregnant and to propitiate comparison of the information between periods, as well as the daily pay-analysis of the content with specialist of the area; methodology of construction of the instrument, opting to the psychometric and use of questionnaire, ahead of the analysis of the advantages, disadvantages and objective of the research; planning of the instrument with the elaboration of the matrix of composed analysis for objective, variable, theoretical references, pointers and type of to be carried through analysis; elaboration of the questions, considering the blocks: partner-demographic characterization, data of health and gynecology-obstetric description, and pregnancy sexuality, as well as the boarding in the questions of all the periods to be evaluated, with the proposal of the transversal boarding “in retrospect” ahead of the limitations of the research with longitudinal accompaniment, where it is suggested boarding of pregnant in the different periods, which answer the referring to the current period and previous questions, also being able to follow in the too much periods; e daily pay-analysis of the questions, eliminating redundant, the unnecessary ones or inappropriate and limiting the extension of the instrument. Had the complexity of the subject, it was elaborated two versions of the Pregnancy Sexuality Questionnaire, one soon and one extended, used as objective of research and sampling. Accomplishment of the process of validation is suggested, reliability and evaluation of the transversal boarding in retrospect, verifying its validity.